The glial fibrillary acidic protein promoter directs sodium/iodide symporter gene expression for radioiodine therapy of malignant glioma - LI, WEI (D.A. Spandidos, 2013)
Radioiodine is a routine therapy for differentiated thyroid cancers. Non-thyroid cancers may be treated with radio-iodine following transfection with the human sodium/iodide symporter (hNIS) gene. The glial fibrillary acidic protein (GFAP) promoter is an effective tumor-specific promoter for gene expression and thus may be useful in targeted gene therapy of malignant glioma. The present study used GFAP promoter-modulated expression of the hNIS gene in an experimental model of radioiodine-based treatment for malignant glioma. Cells were transfected using a recombination adeno-virus and evaluated in cells by studying the transfected transgene expression through western blot analysis, (125)I uptake and efflux, clonogenicity following (131)I treatment and radioiodine therapy using a U87 xenograft nude mouse model. Following transfection with the hNIS gene, the cells showed 95–70-fold higher (125)I uptake compared with the control cells transfected with Ad-cytomegalovirus (CMV)-enhanced green fluorescent protein (EGFP). The western blotting revealed bands of ∼70, 49 and 43 kDa, consistent with the hNIS, GFAP and β-actin proteins. The clonogenic assay indicated that, following exposure to 500 μCi of (131)I-iodide for 12 h, >90% of cells transfected with the hNIS gene were killed. Ad-GFAP-hNIS-transfected and 2 mCi (131)I-injected U87 xenograft nude mice survived the longest of the three groups. The hNIS-expressing tumor tissue accumulated (99m)TcO(4) rapidly within 30 min of it being intraperitoneally injected. The experiments demonstrated that effective (131)I therapy was achieved in the malignant glioma cell lines following the induction of tumor-specific iodide uptake activity by GFAP promoter-directed hNIS gene expression in vitro and in vivo. (131)I therapy retarded Ad-GFAP-hNIS transfected-tumor growth following injection with (131)I in U87 xenograft-bearing nude mice.